A dimensão espacial nas políticas públicas brasileiras de turismo: as possibilidades das redes regionais de turismo - Fratucci, Aguinaldo Cesar (2008)
Aiming at investigating the carelessness towards national politics of spatial dimension as well as possibilities of new governance structures building to appropriate spaces for the tourism from regional networks, this work presents the results of a research developed over the last fifteen years, from the participant's observation of the author within the context of Rio de Janeiro state, specially Agulhas Negras touristic region. Understanding tourism as an outstanding social-spatial phenomenon of contemporariness, it proposes that its study be unfolded through several meta-points-of-view that may include and amplify the complex game of actions, feedbacks and inter-relations established by its many social agents: tourists, businessmen, public power, direct and indirect workers as well as the population who lives in touristic destinies. After discussing about the logic which exists between the social-spatial phenomenon and the economic activity generated by tourism, it presents a review of theoretical foundations necessary to analysis and discussion of touristification processes of spatial stretches, having as reference that tourism is not subjected to these processes, but is the result of actions and interactions of several social agents which produce them. After that, it presents a review of public politics of tourism evolution implemented in Brazil from 1966 on, searching to identify the way spatiality of phenomenon has been dealt by each one of them. Having as observation object the process of touristic area of Agulhas Negras construction, it proposes the adoption of geographical category of net-territory as the most adequate for analysis and study of touristic spaces and points to the tendency of tourism net-territories broadening to the scale of micro-regional and formation of regional tourism networks considered as an opportunity of adopting a new organizational structure of public-private governance, more democratic and participating for development management at a national level.